Leukotriene antagonists reduce epileptic seizures‐related hospitalization in older adult populations with allergic rhinitis or asthma: A population‐based cohort study using the Shizuoka Kokuho database: The Shizuoka study - Yutaro Imaichi; Eiji Nakatani; Yuma Fukutomi; Nagato Kuriyama; Kiyoshi Mori; Akira Sugawara (Epilepsia Open, 2024)
Abstract Objective Managing the risk of epileptic seizures in older adults is increasingly important as the population ages. Leukotriene receptor antagonists (LTRAs) are commonly used to treat asthma or allergic rhinitis. Preclinical studies suggest that LTRAs have antiepileptic effects; however, few population‐based etiological studies on this topic have been available. Our study explored whether LTRAs reduce hospitalization risk associated with epileptic seizures in older individuals with asthma or allergic rhinitis. Methods We conducted a new‐user design analysis using the Shizuoka Kokuho database. We included all individuals aged 60‐89 years who had at least one episode of allergic rhinitis or asthma during the study period. We compared individuals who newly started LTRAs with those who did not take LTRAs. Propensity score matching was used to balance the baseline characteristics of the participants. We compared the hazard ratios for seizure‐related hospitalization between new LTRA users and non‐users and performed subgroup analyses. Results Our matched cohorts consisted of 64 724 new users and non‐users of LTRAs who were aged 60‐89 years and had asthma or allergic rhinitis. During the observation period, 377 (0.58%) and 595 (0.92%) incidents were observed in the LTRA new‐user and non‐user groups, respectively. The hazard ratio for seizure‐related hospitalization was 0.75 (95% confidence interval [CI]: 0.62‐0.92) in the LTRA new‐user group compared with the non‐user group. Subgroup analysis revealed that the hazard ratio was weak in diabetic patients (1.31; 95% CI: 0.72‐2.38). Significance This study indicated that LTRAs reduced seizure‐related hospitalization in older adult patients with allergic rhinitis or asthma. We could not evaluate the severity and related diseases of epileptic seizures during LTRAs. Further studies, including observational studies, detailed multicenter prospective studies, and clinical trials, are needed to validate these findings. Plain Language Summary This study examined if leukotriene receptor antagonists (LTRAs), commonly used for asthma or allergies, could lower seizure risk in older adults. Analyzing health records of 60‐89 year‐olds with asthma or allergies, we found a reduced rate of seizure‐related hospitalizations in those starting LTRAs, though this was not as evident in diabetic patients. Our results suggest potential benefits of LTRAs in preventing seizures in older adults with respiratory issues, but further research is needed to confirm these findings.